2018
DOI: 10.1016/j.jocd.2017.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density and Cross-sectional Geometry of the Proximal Femur Are Bilaterally Elevated in Elite Cricket Fast Bowlers

Abstract: The skeleton of a cricket fast bowler is exposed to a unique combination of gravitational and torsional loading in the form of substantial ground reaction forces delivered through the front landing foot, and anterior-posterior shear forces mediated by regional muscle contractions across the lumbo-pelvic region. The objectives of this study were to compare the hip structural characteristics of elite fast bowlers with recreationally active age-matched controls, and to examine unilateral bone properties in fast b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
3
4
0
1
Order By: Relevance
“…The high BMD at both femoral neck and total hip sites is comparable to elite female athletes participating in high impact sports, such as volleyball (Bellver et al, 2019). There was no significant difference in BMD or section modulus between or within groups (Figure 2), similar to the findings observed in male fast bowlers (Lees et al, 2018). This demonstrates that the total bone loading on the proximal femur is similar between and within positions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The high BMD at both femoral neck and total hip sites is comparable to elite female athletes participating in high impact sports, such as volleyball (Bellver et al, 2019). There was no significant difference in BMD or section modulus between or within groups (Figure 2), similar to the findings observed in male fast bowlers (Lees et al, 2018). This demonstrates that the total bone loading on the proximal femur is similar between and within positions.…”
Section: Discussionsupporting
confidence: 88%
“…Batters, fast bowlers and spin bowlers all demonstrated proximal femur Z‐scores in excess of +2.4 (Table 2), demonstrating the osteogenic potential of participating in cricket at the proximal femur, similar to the findings observed in male fast bowlers (Lees et al, 2018). The high BMD at both femoral neck and total hip sites is comparable to elite female athletes participating in high impact sports, such as volleyball (Bellver et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Based on the search criteria, only five full-member cricket nations have collected some form of data regarding the anthropometrical and morphological characteristics of elite male bowlers and batters. These nations include England (28 studies), 4,2753 Australia (17 studies), 7,25,5468 South Africa (five studies), 16,19,24,69,70 India (one study), 71 and Sri Lanka (one study). 72 Of the published research, most has focused on bowlers (45 studies), with a limited amount of literature directed around batters (12 studies).…”
Section: Resultsmentioning
confidence: 99%
“…The overall cross-sectional area of the internal fixation is positively related to the bending section modulus and the torsion section modulus 16 , 30 . The larger the overall cross-sectional area of the internal fixation indicated the more dispersed stress of the screws in the femoral head, and the less displacement of the fractured end 31 . The results of this study showed that the area ratio of OT configuration was not affected by the three factors of the inclined ellipse, and remains a stable value (0.413).…”
Section: Discussionmentioning
confidence: 99%